Enhancing Indonesian Coffee Competitiveness in the US Market: Competitor Analysis and Development Strategy - Anthony Sheva Sopaheluwakan; M. Taufiq; Anisa Fitria Utami (Cita konsultindo, 2025)
Coffee is one of Indonesia's main plantation commodities with high export value. As the world's leading coffee producer, Indonesia actively exports coffee as part of its national economic strategy. This study aims to analyze the competitiveness and performance of Indonesian coffee exports in the United States market by comparing them with competing countries, namely Brazil, Canada, Italy, and Ethiopia. The methods used in this study are Revealed Comparative Advantage (RCA) and Constant Market Share (CMS). The data analyzed includes global export growth, coffee export value, and total commodity export value from Indonesia and competitor countries during the 2011-2022 period. The results of the study show that although Indonesian coffee has a comparative advantage over Canada and Italy, its competitiveness is still lower than that of Brazil and Ethiopia. In addition, the performance of Indonesian coffee exports to the United States is still relatively weak, with average growth that is below the average world export growth.